And … action?: gender, knowledge and inequalities in the UK screen industries - Ruth Eikhof, Doris; Newsinger, Jack; Luchinskaya, Daria; Rudloff, Daniela (Wiley, 2018)
This article explores how a knowledge ecology framework can help us better understand the production of gender knowledge, especially in relation to improving gender equality. Drawing on Law et al. (2011), it analyses what knowledge of gender inequality is made visible and actionable in the case of the UK screen sector. We, firstly, show (1) that the gender knowledge production for the UK screen sector operated with reductionist understandings of gender and gender inequality, and presented gender inequality as something that needed evidencing rather than changing, and (2) that gender knowledge was circulated in two relatively distinct circuits, a policy- and practice-facing one focused on workforce statistics and a more heterogeneous and critical academic one. We then discuss which aspects of gender inequality in the UK screen industry remained invisible and thus less actionable. The article concludes with a critical appreciation of how the knowledge ecology framework might help better understand gender knowledge production, in relation to social change in the UK screen sector and beyond.